Relating Metacognition of Secondary School Students with their Perceived Teacher Competencies - Kapadia, Rashida; Garg, Indu (JOURNAL OF INDIAN EDUCATION, 2012)
This study investigated metacognition and perceived teacher competencies of secondary school students. Nine hundred twenty Class IX students from schools across Greater Mumbai participated in the study. Gender-wise comparisons were made between the students for the two variables. Female students were found to possess better metacognition and they also perceived teacher competencies more favourably than the male students. The study also aimed at ascertaining the relationship between metacognition and perceived teacher competency scores. Analysis was done for total and component-wise scores for metacognition and perceived teacher competencies. A significant, direct, positive correlation was found between total metacognition and total teacher competency scores. Component-wise analysis revealed technical competency of teachers to be a strong and significant predictor of all the components of metacognition for total sample and for male and female students. This indicates that the metacognition of students is related to teachers’ technical competencies such as communication skill, evaluation ability, classroom management, mastery over content and ability to organise information. The study highlights the need for competent teachers for supporting student’s metacognition.